Konsep Kepribadian Konselor Muslim dalam Al-Qur’an (Tela’ah Surat Al-Ahzab Ayat 21) - Muna, Naelul; Mardiana, Alvy (Department of Islamic Guidance and Counseling, 2023)
This paper aims to examine more deeply about Muslim personality, given the lack of studies on Muslim personality. This study used the library research method, using books as a source of data. The results of this study are the concept of personality in Islam in the Al-Qur’an Al-Ahab verse 21, namely firstly Muslim personality includes attitudes, traits, reactions, actions, and behavior, secondly Muslim personality aims to make a good person in the corridor Islam is like always saying, behaving in accordance with the path outlined by Islam in life.